Estudo da eficiência microbiológica de um sistema de ventilação hospitalar com filtragem HEPA na prevenção de patógenos dispersos no ar - (:unkn) unknown (Universidade Brasil, 2020)
Air conditioning in Intensive Care Centers (ICUs) and Wards is a latent means of propagating microorganisms through the respiratory tract, where patients and health professionals are exposed to etiologic agents transmitted by bioaerosols. In addition, the contagion in these environments confirms the perception that poorly designed air conditioning; it potentiates the transmission of pathogens in places of constant flow of immunosuppressed individuals and, therefore, susceptible to infections. Thus, air conditioning with HEPA filtration presents itself as a hospital engineering technique with an effective potential to reduce the entry of these contaminating agents dispersed in the air. The occurrence of pathogens of this nature has been neglected in scientific research, becoming the object of more recent studies, but which still require a greater volume of debate. Research objective consisted of evaluating the microbiological efficiency of HEPA filtering air conditioning systems in a hospital (CTI and wards), in preventing the spread of airborne lung diseases. The method used was the collection of air samples through the active impaction method, over a period of 32 weeks in the intensive care unit and in the wards. The results identified 67% of fungi and 33% of bacteria with their respective subcategories. The counting of colony-forming units (CFU) was higher than that recommended by the current regulation. The conclusion of the study shows that hospital air is a route of transmission and persistence of multi resistant microorganisms and suggests the need to review the rules that address the use of HEPA filters, laminar flow, negative pressure, air changes, bed validation and detection methodology, necessary in hospital environments.
Keywords: Ambiente hospitalar; Filtro HEPA; Bioaerossóis; Sistemas de Climatização; Engenharia Biomédica (Bioengenharia)